LincRNA‐p21 Impacts Prognosis in Resected Non–Small Cell Lung Cancer Patients through Angiogenesis Regulation. Issue 12 (December 2016) - Castellano, Joan J.; Navarro, Alfons; Viñolas, Nuria; Marrades, Ramon M.; Moises, Jorge; Cordeiro, Anna; Saco, Adela; Muñoz, Carmen; Fuster, Dolors; Molins, Laureano; Ramirez, Josep; Monzo, Mariano
ABSTRACT : Introduction: : Long intergenic noncoding RNA‐p21 (lincRNA‐p21) is a long noncoding RNA transcriptionally activated by tumor protein p53 (TP53) and hypoxia inducible factor 1 alpha subunit (HIF1A). It is involved in the regulation of TP53‐dependent apoptosis and the Warburg effect. We have investigated the role of lincRNA‐p21 in NSCLC. Methods: : LincRNA‐p21 expression was assessed in tumor and normal tissue from 128 patients with NSCLC and correlated with time to relapse and cancer‐specific survival (CSS). H23, H1299, and HCC‐44 cell lines were cultured in hypoxic conditions after silencing of lincRNA‐p21. The TaqMan human angiogenesis array was used to explore angiogenesis‐related gene expression. Levels of the protein vascular endothelial growth factor A were measured by enzyme‐linked immunosorbent assay in the cell supernatants. Angiogenic capability was measured by human umbilical vein endothelial cell tube formation assay. Microvascular density in tumor samples was analyzed by immunohistochemistry. Results: : LincRNA‐p21 was down‐regulated in tumor tissue, but no association was observed with TP53 mutational status. High lincRNA‐p21 levels were associated with poor CSS in all patients ( p = 0.032). When patients were classified according to histological subtypes, the impact of lincRNA‐p21 was confined to patients with adenocarcinoma in both time to relapse ( p = 0.006) and CSS ( p < 0.001). To explain the poor outcome of patients with high lincRNA‐p21 expression, we studied the role of lincRNA‐p21 in angiogenesis in vitro and observed a global downregulation in the expression of angiogenesis‐related genes when lincRNA‐p21 was inhibited. Moreover, supernatants from lincRNA‐p21–inhibited cells were significantly less angiogenic and had lower levels of secreted vascular endothelial growth factor A than controls did. Finally, tumor samples with high lincRNA‐p21 levels had higher microvascular density. Conclusions: : Our findings suggest that lincRNA‐p21 affects outcome in patients with NSCLC adenocarcinoma through the regulation of angiogenesis.